Centering, Affective Regulation, and Exposure (CARE) Group: Mindful Meditation and Movement for Youth with Anxiety. Issue 2 (2nd April 2020) - McDowell, Gina; Valleru, Jahnavi; Adams, Meredith; Fristad, Mary A.
ABSTRACT: Anxiety is common in adolescents, when acuity spikes, higher intensity services may be required. However, it can be challenging to retain these adolescents in ongoing care once a crisis resolves. The aim of this quality improvement study was to evaluate within the crisis management segment of our behavioral health-care system the potential benefit of a mindful movement intervention for reducing anxiety in, and improving retention of acutely anxious adolescents in "bridging" clinical care while waiting for "step-down" (i.e., from inpatient to outpatient) or "step-up" (i.e., high acuity outpatient referrals to clinics with waiting lists) services. We referred 87 "bridging" youth to one of eight 6-session, 90-minute Centering, Affective Regulation, and Exposure (CARE) groups. Most (n = 81, 93%) began and 56 (64%) completed CARE. Pre/post group anxiety scores declined significantly (youth, p <.02; parent, p =.001); qualitative reports were consistent with these findings. Treatment engagement more than doubled (33% to 73% retention) and use of higher intensity services declined (no study participants were readmitted in 30 days or 90 days compared to historical readmission rates of 9.5% for 30 days or 15.6% for 90 days). Results are consistent with previous studies that suggest interventions that include meditation and mindful movement lead to lower emotional dysregulation and anxiety symptoms in youth. Importantly, participants were more likely to remain engaged in outpatient treatment and were less likely to be rehospitalized than prior to the implementation of CARE. Our institution has expanded CARE for youth with transdiagnostic anxiety/depression and has adapted CARE for youth with intellectual/developmental delays. Further empirical investigation appears warranted.